Studies on the response of Daphnia magna to the stresses of sodium cefotaxime and neomycin sulphate(大型溞对头孢噻肟钠与硫酸新霉素胁迫的响应) - 金一凡(JIN Yifan); 刘胤仪(LIU Yinyi); 吴迪(WU Di); 谢大笑(XIE Daxiao); 郭沛涌(GUO Peiyong) (Zhejiang Daxue xuebao. Lixue ban)
In recent years, growing attention has been directed toward the toxicity, persistence, and bioaccumulation of antibiotics due to their extensive utilization. This study investigated the effects of cephalosporin sodium (CS), neomycin sulfate (NS), and their combined exposure (CS+NS) at varying concentration gradients on inhibition rates, growth, and reproduction in Daphnia magna. The dynamic characteristics of superoxide dismutase (SOD) and catalase (CAT) activities, along with reduced glutathione (GSH) content, were analyzed to elucidate the response mechanisms of reproduction and antioxidant systems in D. magna under single and combined antibiotic stress. Key findings include: (1) Both individual and combined antibiotics exhibited concentration-dependent acute toxicity, with 48 h-EC50 values of 0.685, 6.24×10-4, and 0.810 mg·mL-1 for CS, NS, and CS+NS, respectively. (2) Reproductive traits demonstrated particular vulnerability to antibiotic stress. Low-concentration CS/NS exposure delayed initial neonate production, whereas high concentrations accelerated this process. Conversely, combined CS+NS exposure progressively delayed initial reproduction with increasing concentrations. All treatments reduced initial neonate counts. (3) Differential responses were observed in SOD/CAT activities and GSH levels under various antibiotic exposures. These findings systematically reveal the distinct adaptation mechanisms of D. magna to antibiotic-induced oxidative stress through antioxidant regulation and reproductive adjustments.近年来，随着抗生素的广泛使用，其毒性、持久性和生物累积性受到高度重视。以大型溞（Daphnia magna）为实验对象，分析了不同浓度梯度的头孢噻肟钠（CS）、硫酸新霉素（NS）胁迫及CS+NS复合胁迫对大型溞的抑制率、生长、繁殖等的影响，探讨了大型溞超氧化物歧化酶（SOD）、过氧化氢酶（CAT）活性及还原型谷胱甘肽（GSH）含量的动态变化特征，揭示了大型溞繁殖与抗氧化系统对单一和复合抗生素胁迫的响应机制。结果表明：（1）单一及复合抗生素对大型溞的急性毒性均随其浓度的增加而增大，对大型溞的抑制作用也随其浓度的增加逐渐增强。在CS，NS及CS+NS胁迫下，大型溞的48 h-EC50分别为0.685，6.24×10-4，0.810 mg·mL-1。（2）CS，NS及CS+NS对大型溞的毒性作用主要体现在繁殖特征上。在低浓度单一抗生素（CS或NS）胁迫下，大型溞首次产溞时间延后，高浓度大型溞首次产溞时间提前；在CS+NS复合胁迫下，大型溞首次产溞时间随浓度的增加呈逐渐延后的趋势。在抗生素胁迫下，大型溞首次产溞数量均有不同程度减少。（3）CS，NS及CS+NS胁迫对大型溞SOD活性、CAT活性和GSH含量的影响各不相同。